Pyridopyrimidinone Derivatives as DNAG‐Quadruplex‐Stabilizing Agents: Design, Synthesis and Biophysical Studies. Issue 18 (28th June 2017) - Malhotra, Rajesh; Rarhi, Chhanda; Diveshkumar, K. V.; Bommisetti, P.; Pany, Sushree Prangya P.; Roy, Subho; Pradeepkumar, P. I.; Kundu, Mrinalkanti
Abstract: DNA can fold into non‐canonical structures such as G‐quadruplexes (G4 s) in addition to adopting the double helical structure. Considering the relationship between stabilization of G4 structure and anticancer effects, development of G4 interactive compounds has been of significant interest. Past years have witnessed the discovery of scaffolds targeting G4 structures based on planar, multi‐aromatic ring compounds. With an aim to engineer drug‐like properties, we designed and synthesized pyridopyrimidinone based selective G4 DNA stabilizing agents 1–3, and further they were evaluated for G4 DNA recognition properties. CD melting studies revealed the preferential stabilization of parallel topology of promoter c‐MYC and c‐KIT G4 DNAs by the ligands, especially 2 and 3, over the different topologies of telomeric G4 DNA. UV melting experiments suggested that no significant stabilization was observed for duplex DNA. Further, the results from ITC experiments substantiated the preferential stabilization of parallel topology of c‐MYC G4 DNA over telomeric and duplex DNA by the ligands 2 . These data showed that ligand 2 has moderate binding affinity to the c‐MYC G4 DNA and is ∼49‐fold and ∼25‐fold selective over the telomeric G4 DNA and the duplex DNA respectively. The molecular modeling and dynamics studies of the ligand 2 in complex with c‐ MYC and c ‐ KIT1 G4 DNAs showed that this ligand stacks on the 5′‐quartet of c ‐ MYC and 3′‐quartet of c ‐ KIT1 G4 DNA structures. Abstract : Pyridopyrimidinone based selective, drug‐like G4 DNA stabilizing agents 1–3 have been designed, synthesized and evaluated for G‐quadruplex (G4) DNA recognition properties using CD melting, UV melting, and ITC experiments. The data demonstrate that ligand 2 has moderate binding affinity to the c‐MYC G4 DNA and is ∼49‐fold and ∼25‐fold selective over the telomeric G4 and the duplex DNAs respectively. Further, the mode of binding of ligand 2 with c‐MYC and c‐KIT1 G4 structures have also been probed using computational studies.